Implementasi Literasi Melalui Pembelajaran Ipas Berbasis Permainan Puzzle Untuk Siswa Sekolah Dasar - Nanda Ayu Setiawati; Dabukke, Barita Esman; Robinson Hutagoal (Universitas Sari Mutiara Indonesia, 2024)
This study aims to develop the literacy skills of elementary school students through Science and Social Studies (IPAS) learning based on puzzle games. This research uses a qualitative descriptive method to analyze and describe the improvement in students' literacy skills after the implementation of puzzle-based learning media. The subjects of the study were fifth-grade students at an elementary school in Medan. Data collection was carried out through observation, interviews, and document analysis. The results of the study show that the use of puzzle games in IPAS learning can improve students' literacy skills, particularly in reading, understanding concepts, and problem-solving. Students demonstrated increased interest and motivation in learning, as well as the ability to think critically and creatively. Additionally, interactions among students during the puzzle games also contributed to the development of social skills and cooperation. The conclusion of this study is that IPAS learning based on puzzle games is an effective method to enhance elementary school students' literacy skills. It is hoped that the results of this study can serve as a reference for teachers and educators in developing innovative and enjoyable learning strategies.